Epistemology of End-Time Riots in the View of Islam: A Study on Surah Al-Zalzalah: 1-5 - Dania Deby Trisia; Muthoifin (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
The purpose of this study was to analyze the events of the end-time riots and their signs contained in the Qur'an Surah Al-Zalzalah verses 1-5. The data collection technique is by examining documents, primary from books of commentary and secondary data from books that discuss themes that are directly and indirectly related to this research, using a normative approach. The results of this study reveal that the signs of an end-time riot according to the Islamic view are the occurrence of various eschatological events such as a great shock (earthquake), the earth releases the burden that is in its womb, there will be panic and confusion. everywhere, and people about the events of the end of time are lamenting and regretting the fate of their wealth.